Comparative Proteomic Insights into the Immune Response of Conogethes punctiferalis Challenged with Beauveria bassiana - Shaohua Li; Zhiwei Kang; Xiangdong Li; Hailei Wei; Xiangchu Yin; Fangqiang Zheng; Fanghua Liu (Insects, 2025)
The yellow peach moth (YPM), Conogethes punctiferalis, is an important agricultural insect pest causing severe damage to corn in eastern China. Beauveria bassiana is an effective, eco-friendly, and promising alternative agent for controlling this insect pest. However, insect immunity can limit the ability of fungal infections. In order to understand the immune response mechanism of YPM, a comparative proteomic analysis of non-infected and B. bassiana-infected larvae was conducted using the isobaric tags for relative and absolute quantification (iTRAQ) technique. On the basis of proteomic analysis, 4195 quantifiable proteins were identified from a total of 29,155 peptides. The functions of the identified proteins were annotated in four databases (GO, COG, KEGG, and IPR). A total of 132 immune-related proteins were screened, including 46 pathogen recognition proteins, 27 extracellular signal modulation proteins, and 59 immune effectors. Furthermore, 70 differentially expressed proteins (DEPs) were identified, including 57 up-regulated proteins and 13 down-regulated proteins. Among these, four DEPs were related to immunity, namely one defense protein and three peptidoglycan recognition proteins. Six randomly selected immune-related proteins associated with target genes were validated for qRT-PCR, and the results indicated that the accuracy and reliability of the proteome sequencing data were high. Taken together, the results enrich the fundamental knowledge of YPM immune responses to B. bassiana infection and provide a new insight into insect−pathogen interactions.